RICHELIEU CROSSROADS OF THE PHILOSOPHY OF COSMISM - Мозгова, Н. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
Mykola Fedorovych Fedorov (1829-1903) – at the Richelieu Lyceum (city of Odessa). The aim of the study is to clarify the ideological coincidence of the main provisions of M. Fedorov’s "Philosophy of the Common Cause" and philosophy lectures of Y. Mikhnevych delivering in the Rishelieu Lyceum in 1849-1851. The tasks are: to analyze the main ideas of M. Fedorov’s "Philosophy of the Common Cause" and reveal the ideological preferences of a representative of the spiritual and academic philosophy Y. Mikhnevych, and then to unveil the ideological coincidences of the main provisions of M. Fedorov’s project and the lectures of Y. Mikhnevych, thus substantiating the fact of the influences of philosophers of Kyiv school of spiritual and academic philosophy of the ХІХ century on the formation of the concept of Russian cosmism. Research methods. In the process of the study hermeneutic method – for explaining and interpreting the authentic texts of M. Fedorov and Y. Mikhnevich; method of historiographical analysis – for systematization of primary sources and scientific literature devoted to "Philosophy of the Common Cause" of M. Fedorov and the philosophical and anthropological concept of Y. Mikhnevych; comparative-historical method – for identification socio-historical conditions which the philosophical views of both thinkers were formed in; comparative analysis – for comparing philosophical preferences of M. Fedorov and Y. Mikhnevych; method of textual analysis – for the study of the context the philosophical heritage of both thinkers has been studied – were used. Research results. To categorically assert the existence of the direct influence of Y. Mikhnevych on the formation of M. Fedorov’s doctrine, one should find the direct recognition of this influence in the texts of the latter. However, we have not yet found such a direct recognition of influence in Fedorov's works. Therefore, our reflections are still hypothetical. We hope for their confirmation, although refutation in science is also no less positive than proof. Conclusions. The author has every reason to assert that the anthropological, natural philosophical and epistemological views of Y. Mikhnevych could be productive in terms of inducing the main principles of M. Fedorov’s Project of the Common Cause. It can also be asserted that the views of both thinkers are of indisputable content affinity.